Creating business agility : how convergence of cloud, social, mobile, video, and big data enables competitive advantage - Heisterberg, Rodney J.; Verma, Alakh, 1963- (New Jersey : John Wiley & Sons, Inc., 2014)
"Creating Business Agility: How Convergence of Cloud, Social, Mobile, Video, and Big Data Enables Competitive Advantage provides a game plan for integrating technology to build a smarter, more customer-centric business. Using a series of case studies as examples throughout, the book describes the agility that comes from collaborative commerce, and provides key decision makers the implementation roadmap they need to build a successful business ecosystem. The focus is on Business Agility Readiness in terms of the five major changes affecting the information technology landscape, and how data-driven delivery platforms and decision-making processes are being reinvented using digital relationships with a social business model as the consumer world of technology drives innovation and collaboration. Cloud computing, social media, next-gen mobility, streaming video, and big data with predictive analytics are major forces now for a competitive advantage, and Creating Business Agility provides leaders with a roadmap for readiness. Business leaders tasked with innovation and strategy will find that Creating Business Agility provides important insight from an informed perspective"--
"Focuses on the technology innovations that may help in building virtual businesses and making existing businesses smarter and efficient in their operations. Intended to help key decision makers understand more about introducing new technologies into businesses"--
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Technological innovations -- Management; Information technology -- Management; Organizational effectiveness; Strategic planning; BUSINESS & ECONOMICS -- General; Information technology -- Management; Organizational effectiveness; Strategic planning; Technological innovations -- Management; Electronic books